Laudato Si, Environmental Theology and the Leadership of Pope Francis - Kriswibowo, Arimurti; Amtiran, Abdon (East Asian Journal of Multidisciplinary Research, 2024)
This article explores the interaction between environmental theology and leadership in the context of Pope Francis' "Laudato Si'", with a particular focus on the role of Christian leaders in addressing environmental issues. Using descriptive qualitative methods, the study analyses the encyclical "Laudato Si'" and related Catholic Church documents. The article finds that theological concepts such as "Salvation and Liberation,""Obedience to God the Creator," and "Social and Ecological Justice" play an important role in shaping Christian leaders' attitudes and actions towards the environment. This article provides insights into how Christian leadership can inspire and mobilise environmentally responsible action, showing that this responsibility is not only a moral imperative, but also an expression of deep Christian faith.